Multi-sensori dalam konsepsi tempat pada lingkungan cagar budaya perkotaan - Eggi Septianto; Michael Isnaeni Djimantoro; Patricia Pahlevi Noviandri; Firmansyah; Heru Wibowo Poerbo; Widjaja Martokusumo (ARTEKS : Jurnal Teknik Arsitektur, 2023)
Individuals' multi-sensory experiences play an essential role in understanding a place of cultural significance. Understanding urban area/environment in the conception of a place is not limited to physical aspects alone. This understanding contradicts to the common paradigm in cultural heritage conservation, which is still limited to improving physical quality based on visual senses. This study aims to discuss the role and potential of multi-sensory in understanding the concept of place, which is beneficial to the conservation of urban heritage areas. This study employs the content analysis method with data from library studies and field observations of cultural heritage areas in and around Gedung Sate, Bandung. The results demonstrate that multi-sensory perception plays a pivotal role and has the potential to facilitate the process of reading and understanding its sense of place. This discussion opened a new discourse to integrate non-physical aspects based on subject perceptions in discussions on urban heritage areas.